Comparative evaluation of subclavian vein catheterization by supraclavicular and infraclavicular approach - Kiwi Mantan; Sandeep Kothari; Shiva Tanwar; Satyaprakash; Jinesh Baid; Gaurav Joshi (Journal of Applied Pharmaceutical Research, 2022)
The present study was conducted in Department of Anaesthesia, Sardar Patel Medical College and PBM Hospital, Bikaner, with the aim of comparative evaluation of subclavian vein catheterization by supraclavicular and infraclavicular approach. There are three common routes of central venous catheterization i.e. subclavian, internal jugular and the femoral. Hence in our study we have done a comparative evaluation of supraclavicular and infraclavicular approach for SCV catheterization with primary objective of successful catheterization of SCV using anatomical landmark technique and secondary objective of first attempt success rate, time taken for cannulation and also record the incidence of complications related to either approach. In our study, 60 patients enrolled were randomly divided into two groups of 30 patients each. In Group A Infraclavicular SCV catheterization and in Group B Supraclavicular catheterisation was performed using anatomical landmark approach. Successful catheterization, first attempt success rate, time taken for venous access and catheterization, catheter malfunction or any other complication were recorded. In group A (IC) Maximum 63.33% were inserted in single attempt whereas minimum 10% required 3 or more attempts while in group B (IC) maximum 93.33% were inserted in single attempt whereas minimum 3.33% needed 3 or more attempts, and the difference was found statistically significant. Overall successful catheterization was 90% in Group A and 96% in Group B while 93 % when combined for both groups. Mean time taken for insertion was observed more (6.67 ± 1.44 min.) in group A whereas less (4.47 ± 1.01min.) in group B, and the difference was found statistically highly significant. We conclude that SC approach of SCV catheterization is better as comparable to IC approach in terms of landmarks accessibility, success rate, time taken and rate of complications.